Minimally Invasive Surgery for Intracerebral and Intraventricular Hemorrhage - Zheng, Zelong; Wang, Qi; Sun, Shujie; Luo, Jinbiao (Frontiers in Neurology, 2022)
Spontaneous intracerebral hemorrhage (ICH), especially related to intraventricular hemorrhage (IVH), is the most devastating type of stroke and is associated with high mortality and morbidity. Optimal management of ICH remains one of the most controversial areas of neurosurgery and no effective treatment exists for ICH. Studies comparing conventional surgical interventions with optimal medical management failed to show significant benefit. Recent exploration of minimally invasive surgery for ICH and IVH including catheter and mechanical-based approaches has shown greater promise. Early phase clinical trials have confirmed the safety and preliminary treatment effect of minimally invasive surgery for ICH and IVH. Pending efficacy data from phase III trials dealing with diverse minimally invasive techniques is likely to shape the treatment of ICH.